Carta editorial - Ruíz, Adi E. Lazos; Larrain, Alina Álvarez; Kropf, Marcela Stuker; Miraglia, Marina; Dutra e Silva, Sandro (Historia Ambiental Latinoamericana y Caribeña (HALAC) revista de la Solcha, 2021)
Carta editorial